Hubungan Perilaku Vaginal Hygiene dan Kejadian Leukorea Pada Remaja - Zougira, Nelvada; Shintya, Lea Andy (Fakultas Ilmu Keperawatan Universitas Klabat, 2024)
Leukorrhea is an occurrence that occurs in women, where the fluid discharge occurs from the vagina, does not feel itching and does not smell, on the contrary that is a concern when leukorrhea smells, and itches for that reason to avoid abnormal leukorrhea is important for teenagers to carry out proper vaginal hygiene. The purpose of this study is to find out the relationship between vaginal hygiene behaviour and the occurrence of leukorrhea in teenagers. Research method is the descriptive correlation using the Cross Sectional approach. Sampling was carried out purposive sampling with a total sample of 199 respondents. The results of the study showed vaginal hygiene behaviour of 199 respondents there were as many as 164 respondents (82.4%) in the good category and 35 respondents (17.6%) with the bad category, for the incidence of leukorrhea as much as 178 respondent (89.4%) on the normal category and 21 respondents (10.6%) at the abnormal category. There's a connection between vaginal hygiene behaviour and the occurrence of leukorrhea in teenagers, with a p-value of 0.020 < 0.05. The recommendation for teenagers to maintain good vaginal behavior and for the following researchers it is recommended to study the factors of knowledge, attitudes, daily activities Lekorea merupakan suatu kejadian yang terjadi pada wanita, dimana terjadinya pengeluaran cairan dari vagina berwarna bening, tidak terasa gatal dan tidak berbau, sebaliknya yang menjadi perhatian bila leukorea berbau, dan terasa gatal oleh sebab itu untuk menghindari leukorea yang tidak normal penting bagi remaja untuk melakukan vaginal hygiene yang benar. Tujuan penelitian ini untuk mengetahui hubungan antara perilaku vaginal hygiene dengan kejadian leukorea pada mahasiswi. Metode penelitian yaitu deskriptif korelasi dengan menggunakan pendekatan Cross-Sectional. Pengambilan sampel dilakukan purposive sampling dengan jumlah sampel 199 responden. Hasil penelitian didapati perilaku vaginal hygiene dari 199 responden terdapat sebanyak 164 responden (82,4%) pada kategori baik dan 35 reponden (17,6%) dengan kategori buruk, untuk kejadian leukorea sebanyak 178 responden (89,4%) pada kategori normal dan 21 responden (10,6%) pada kategori tidak normal. Ada hubungan antara perilaku vaginal hygiene dengan kejadian leukorea pada remaja, dengan nilai p-value 0,020 < 0.05. Rekomendasi bagi remaja tetap mempertahankan perilaku vaginal yang baik dan untuk peneliti berikut disarankan untuk meneliti faktor pengetahuan, sikap, aktivitas sehari-hari.